Introduction: households and landscapes. Issue 3 (26th May 2016) - Foxhall, Lin
ABSTRACT: This issue explores how households, both individually and collectively as communities, choose to embed themselves in landscapes. In different ways and at different scales, the articles explore how their actions shaped, defined and delineated their landscapes through everyday practices.